Manajemen Program Hafalan Quran di Pondok MAS Subulussalam Madina - Lubis, Amrul Aziz; Pasaribu, Munawir (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research analyzes the management of the Al-Quran memorization program at the MAS Subulussalam Madina Islamic Boarding School. This Islamic boarding school has a high commitment to learning to memorize the Al-Quran to produce a Koranic generation that practices religious teachings in everyday life. The challenges faced include limited resources, less varied learning methods, as well as problems with student motivation and discipline. In overcoming these challenges, program management needs to use innovative strategies, careful resource management, development of varied learning methods, as well as coaching and appropriate approaches to student motivation and discipline. Synergy and participation from various parties, such as teaching staff and parents, are also the keys to the success of the Al-Quran memorization program at this Islamic boarding school. This research uses a qualitative approach and case study method, and was obtained through observation, in-depth interviews and document analysis. It is hoped that the results of this research will provide valuable input to improve the quality and effectiveness of Al-Quran memorization programs in Islamic boarding schools, as well as encouraging further research in the field of management of religious education programs in traditional Islamic educational institutions.